The influential factors on awareness towards recycling programs implemented by Perbadanan Putrajaya a study on residents in Precinct 9 / Nur Ezza Maizura Abd Rahim and Nur 'Aisyah Amlir - Abd Rahim, Nur Ezza Maizura; Amlir, Nur 'Aisyah (Faculty of Administrative Science and Policy Studies, 2013)
Recycling is a process to change materials into new products to prevent waste of potentially useful materials, reduce the usage of fresh raw materials, reduce energy consumption, reduce air pollution and water pollution by reducing the need for "conventional" waste disposal, and lower greenhouse gas emissions. On top of that, recycling also is a key component of current waste reduction and is the third component of the "Reduce, Reuse, Recycle" waste hierarchy. The awareness of recycling can help to prevent any barriers that may discourage people from supporting the initiative. This study will discuss about the awareness of Recycling Programs among Precinct 9 Residence that implemented by Perbadanan Putrajaya. The outcomes of this study showed that almost all the influential factors stated does give the contribution towards the awareness of the recycling programs.